Whom to Cater to?: The Challenges and Choices of Jesuit Education in Ranchi, 1947–1960s - Goddeeris, Idesbald (Social sciences and missions, 2024)
After 1947, the Jesuit province of Ranchi faced several challenges: the context of a newly independent country, increasing modernization and industrialization, and growing societal diversity resulting from immigration and urbanization. The Jesuits not only needed to upgrade their primary education, but also had to meet a rising demand for more middle and high schools. They had to make choices: Should they keep uplifting marginalized communities? Or should they cater to the middle class and elite? This article, predominantly based on internal documents of the Society of Jesus in Ranchi, demonstrates that the Jesuits did not make clear decisions and invested their energy in various types of schools and students. As a result, problems and internal discussions persisted.